2018
DOI: 10.1093/trstmh/try093
|View full text |Cite
|
Sign up to set email alerts
|

Expanding home-based management of malaria to all age groups in Rwanda: analysis of acceptability and facility-level time-series data

Abstract: Services were shifted to CHWs, as demonstrated by the number of individuals treated through the expanded program. The rate of severe malaria increased immediately after implementation within intervention districts relative to controls, potentially because of enhanced case-finding. The rate of increase in severe cases was lower in the intervention districts comparatively, likely due to expedited treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…Rwanda achieved substantial reductions in malaria during 2006-2011, partly due to home-based management using artemether/lumefantrine (6). In 2010, at our study site in Huye district, southern Rwanda, we observed a pattern in the P. falciparum multidrug resistance: 1 gene suggestive of intense artemether/ lumefantrine drug pressure, whereas K13 mutations were absent.…”
mentioning
confidence: 65%
“…Rwanda achieved substantial reductions in malaria during 2006-2011, partly due to home-based management using artemether/lumefantrine (6). In 2010, at our study site in Huye district, southern Rwanda, we observed a pattern in the P. falciparum multidrug resistance: 1 gene suggestive of intense artemether/ lumefantrine drug pressure, whereas K13 mutations were absent.…”
mentioning
confidence: 65%
“…Efforts in this direction are being made, both to improve affordability of quality-assured ACTs, and their availability in remote areas 53 54. Expanding access to treatment can be implemented by community-health workers, as recently reported in Rwanda 55. This type of approach can also reduce the time required to obtain treatment, as the need to travel to a health centre is removed.…”
Section: Discussionmentioning
confidence: 99%
“…Madagascar is among several countries in sub-Saharan Africa considering expanding access to mCCM for older populations to address recent increases in malaria transmission rates and persistently low rates of care-seeking behaviour. Malaria prevalence in Madagascar is markedly heterogeneous, but has increased overall since 2010 as evidenced by both routine surveillance data and analyses of data from several Malaria Indicator Surveys (MIS) [ 7 10 ]. The World Health Organization (WHO) estimates malaria incidence to have increased from 42 cases per 1000 individuals in 2010 to 76 cases per 1000 people in 2019 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of malaria-attributable deaths showed an analogous increase during the same time by WHO estimations, from 10 to 18 per 100,000 population [ 10 ]. Based on data from the 2016 MIS, an estimated 46% of CU5 with febrile illness were seen by a provider for care/advice [ 7 ]. Only 15.5% of CU5 with fever had blood taken for a diagnostic malaria test [ 7 ], despite national guidelines recommending that all individuals suspected to have malaria be tested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation